Quercetin inhibits the amphiregulin/EGFR signaling‐mediated renal tubular epithelial‐mesenchymal transition and renal fibrosis in obstructive nephropathy. (11th October 2022) - Wang, Qi; Wang, Fuqiang; Li, Xiangze; Ma, Zhi; Jiang, Dapeng
Abstract: Quercetin is a widely distributed, bioactive flavonoid compound, which displays potential to inhibit fibrosis in several diseases. The purpose of our study was to determine the effect of quercetin treatment on renal fibrosis and investigate the mechanism. Human proximal tubular epithelial cells (HK‐2) stimulated by transforming growth factor‐β1 (TGF‐β1) and a rat model of unilateral ureter obstruction (UUO) that contributes to fibrosis were used to investigate the role and molecular mechanism of quercetin. PD153035 ( N ‐[3‐Bromophenyl]‐6, 7‐dimethoxyquinazolin‐4‐amine) was used to inactivate EGFR (epidermal growth factor receptor). The level of fibrosis, proliferation, apoptosis, and oxidative stress in HK‐2 were measured. All data are presented as means ± standard deviation (SD). p ‐value < .05 was considered statistically significant. In UUO rats, quercetin reduced the area of fibrosis as well as inflammation, oxidative stress, and cell apoptosis. In cultured HK‐2 cells, quercetin significantly ameliorated the EMT induced by TGF‐β1, which was accompanied by increased amphiregulin (AREG) expression. Moreover, quercetin inhibited AREG binding to the EGFR receptor, thereby further affecting other downstream pathways. Quercetin may alleviate fibrosis in vitro and in vivo by inhibiting the activation of AREG/EGFR signaling indicating a potential therapeutic effect of quercetin in renal fibrosis.